The spindle checkpoint and chromosome segregation in meiosis - Gorbsky, Gary J. (FEBS J, 2015)
The spindle checkpoint is a key regulator of chromosome segregation in mitosis and meiosis. Its function is to prevent precocious anaphase onset before chromosomes have achieved bipolar attachment to the spindle. The spindle checkpoint comprises a complex set of signaling pathways that integrate microtubule dynamics, biomechanical forces at the kinetochores, and intricate regulation of protein interactions and post-translational modifications. Historically, many key observations that gave rise to the initial concepts of the spindle checkpoint were carried out in meiotic systems. In contrast with mitosis, the two distinct chromosome segregation events of meiosis present a special challenge for the regulation of checkpoint signaling. Preservation of fidelity in chromosome segregation in meiosis, controlled by the spindle checkpoint, also has significant impact in human health. This review highlights the contributions from meiotic systems in understanding the spindle checkpoint as well as the role of checkpoint signaling in controlling the complex divisions of meiosis.